(untitled) (Bangladesh Journal of Neuroscience, 2018)
Joubert Syndrome is a rare autosomal recessive disorder characterized by hypotonia, ataxia, breathing difficulties, developmental delay with hallmark molar tooth appearance in MRI. We report a rare case of adulthood Joubert Syndrome which is an unusual presentation. A 25 -years male presented to our outpatient department with developmental delay, dysphasia, ataxia, nystagmus, bilateral optic atrophy and hyperreflexia. MRI Brain showed classical ‘molar tooth’ appearance of cerebellar peduncles. Although an uncommon disorder, it is important to diagnose the condition early as physiotherapy and rehabilitation can be effective in coping with the symptoms causing developmental delay. Bangladesh Journal of Neuroscience 2018; Vol. 34 (1): 58-62